Organisational barriers in working with child sexual abuse (Csa) cases: the Malaysian professionals’ experiences. - Salina Nen; Jill Astbury (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
The purpose of this study is to examine organisational barriers faced by professionals working with child sexual abuse (CSA) cases in Malaysia. This study was conducted from a diverse sample of 18 social workers, medical social workers, counsellors and police officers who worked in CSA cases.These participants came from different organisations namely the royal police of Malaysia, the welfare department, hospitals and non-government agency. A qualitative approach was used for collecting and analysing data; and semi structured interview was used to guide the interview. Two main factors had been identified as barriers in working with CSA cases, namely within and between organisations. In terms of within organisations, participants identified factors such as inadequate support, excessive workload, safety issue and lack of resources as the major barriers. As for between organisations,factors such as conflict of power and disorganised system were mentioned as factors preventing capabilities of professionals in giving help. This paper provides an in depth analysis of major barriers facing by professionals working with CSA in Malaysia.